O6 Ideal age to screen for Barrett's oesophagus and oesophageal adenocarcinoma: modelling from the cytosponge-BEST3 trial. (19th June 2022) - Keith Tan, W; Maroni, Roberta; Offman, Judith; Pietro, Massimiliano di; Honing, Judith; O'Donovan, Maria; Sasieni, Peter; Fitzgerald, Rebecca
Abstract : Introduction: Screening for Barrett's oesophagus (BO) is a consideration due to the high mortality from oesophageal adenocarcinoma (OAC). The aim of this study was to utilise data from the randomised controlled Barrett's oEsophagus Screening Trial 3 (BEST3) to estimate: 1) the optimal age for screening of BO/OAC; and 2) the number of missed cases under current primary care reflux referral pathway. Methods: Individuals in the BEST3 who swallowed the Cytosponge (n=1654) were included. For aim 1, we used the positive-predictive value (PPV) of the Cytosponge for a diagnosis of BO/OAC as a proxy for the disease prevalence in the community and modelled the probability of a diagnosis of BO/OAC. Both analyses were stratified by age and sex. For aim 2, we used the BEST3 intervention (n=6834) and control arm (n=6388) data to estimate the number of missed BO/OAC under current reflux referral pathway. Results: Using a 5% risk cut-off for undiagnosed BO/OAC, the ideal age for screening males and females with reflux is 55–79, and 65–79 years, respectively ( Figure 1 ). The overall PPV for a diagnosis of BO/OAC were 65% (95% CI 57–73%) for males and 50% (95% CI 39–61%) for females. The number of missed BO/OAC was estimated using BEST3 data. There were 16/6388 (0.3%) and 131/6834 (1.9%) cases of BO/OAC diagnosed among those randomised to usual care or who had the Cytosponge, respectively. If we correct for those who were: randomised to the Cytosponge group but did not accept the offer (5180/6834, 78.8%); unable to swallow the Cytosponge (96/1750, 5.5%); declined confirmatory endoscopy (10/231, 4.3%); and those with a false negative diagnosis - based on the random sample who were invited for endoscopy at end of the study among the TFF3 negative group (2/64, 3.1%); we estimate that 680 cases of BO/OAC among the 6388 individuals in the controls, and 500 of these could have been screen-detected if all had attempted to swallow a Cytosponge. Compared to 16 cases of BO/OAC identified through usual care, 97.6% of BO/OAC are likely to be missed using the current referral pathway and 73.5% of undiagnosed disease could be detected by screening. Conclusion: A Cytosponge-based screening strategy for BO/OAC could include males aged 55–79 and females aged 65–79; depending on uptake rates, it would allow us to discover a greater proportion of the 97.6% estimated missed BO/OAC in the community.